Effect of Self-Monitoring of Blood Pressure on Diagnosis of Hypertension During Higher-Risk Pregnancy: The BUMP 1 Randomized Clinical Trial. Issue 11 (November 2022) - Tucker, Katherine L.; Mort, Sam; Yu, Ly-Mee; Campbell, Helen; Rivero-Arias, Oliver; Wilson, Hannah M.; Allen, Julie; Band, Rebecca; Chisholm, Alison; Crawford, Carole; Dougall, Greig; Engonidou, Lazarina; et al.
ABSTRACT: (Abstracted from JAMA 2022;327:1656–1665 It is estimated that approximately 10% of pregnancies worldwide in 2019 were affected by elevated blood pressure (BP). The United Kingdom has previously reported inadequate monitoring of elevated BP as a significant contributing factor to maternal death.